Establishing the Validity of the Internet-Based Bill-Paying Task to Assess Executive Function Deficits Among Adults With Traumatic Brain Injury. - Nadler Tzadok, Yael; Eliav, Rotem; Portnoy, Sigal; Rand, Debbie (American Journal of Occupational Therapy)
Importance: Executive function (EF) deficits are common after traumatic brain injury (TBI). During rehabilitation, it is important to identify EF deficits and understand their impact on daily function. The internet-based Bill-Paying Task, modified from the Executive Function Performance Test, has not yet been validated for use with people with TBI. Objective: To examine the known-groups, convergent, and ecological validity of the internet-based Bill-Paying Task for assessing EF deficits after TBI. Design: Cross-sectional study with two consecutive parts based on the study's objectives. Setting: Inpatient rehabilitation and community. Participants: Part 1 included 42 adults with TBI and 47 healthy adults; Part 2 included 28 of the 42 adults with TBI. Measures: Assessments included the Internet-based Bill-Paying Task, WebNeuro neurocognitive computerized battery, Semantic Verbal Fluency test, Behavioural Assessment of the Dysexecutive Syndrome (BADS), Dysexecutive Questionnaire (DEX), and cognitive items of the FIM® and the Functional Assessment Measure (cognitive FIM+FAM). Results: For Part 1, participants with TBI required significantly more cues and longer completion time to perform the internet-based Bill-Paying Task. For Part 2, moderate significant correlations were found between the internet-based Bill-Paying Task total score and the WebNeuro, Semantic Verbal Fluency test, BADS, DEX, and cognitive FIM+FAM. Conclusions and Relevance: This study supports the known-groups, convergent, and ecological validity of the internet-based Bill-Paying Task for assessing EF deficits among adults with preserved basic cognitive abilities after TBI. Therefore, it can be used to assist with rehabilitation treatment planning after TBI. What This Article Adds: The internet-based Bill-Paying Task, an online payment task relevant to today's technological world, is valid to assess higher cognitive abilities of people after a traumatic brain injury. This assessment may contribute to a better understanding of patients' cognitive profiles and their potential impact on daily performance. This study supports the validity and use of the internet-based Bill-Paying Task to identify executive function (EF) deficits and understand the impact on daily function for people with traumatic brain injury (TBI). The Bill-Paying Task can be used to assist with rehabilitation treatment planning for people with TBI.